Differential Drug Release Kinetics from Paclitaxel-Loaded Polydioxanone Membranes and Capsules - Padmakumar, Smrithi; Varghese, Merin M.; Menon, Deepthy (Recent Advances in Drug Delivery and Formulation, 2022)
Background: Drug laden implantable systems can provide drug release over several hours to years, which eventually aid in the therapy of both acute and chronic diseases. The present study focuses on a fundamental evaluation of the influence of implant properties such as morphology, architecture, porosity, surface area, and wettability in regulating the drug release kinetics from drug-loaded polymeric matrices. Methods: For this, Polydioxanone (PDS) was selected as the polymer and Paclitaxel (Ptx) as the model drug. Two different forms of the matrix implants, viz., reservoir type capsules developed by dip coating and matrix type membranes fabricated by phase inversion and electrospinning, were utilized for the study. Drug release from all the four different matrices prepared by simple techniques was evaluated in vitro in PBS and ex vivo in peritoneal wash fluid for 4 weeks. The drug release profiles were thereafter correlated with the physicochemical parameters of the polymeric implants. Results: Reservoir-type capsules followed a slow and steady zero-order kinetics, while matrix-type electrospun and phase inversion membranes displayed typical biphasic kinetics. Conclusion: It was inferred that the slow degradation rate of PDS polymer as well as the implant properties like porosity and wettability play an important role in controlling the drug release rates.
Keywords: electrospinning